Teaching and learning intervention in the educational setting: adapting the teacher theory model - Leovigildo Lito D. Mallillin (Universitas Majalengka, 2022)
The study aims to examine the teaching and learning intervention in the educational setting as implemented in terms of student interest, learning reflection, direct instruction, learning activities, and student performance. It also aims to identify the contribution of the teacher theory model in adapting the teaching and learning intervention in the educational setting in the area of talented, enthusiastic, adaptability, creativity, honest, effective, and resourceful. The research employs the descriptive quantitative methods and designs to utilize and generalize the result of the opinion, attitude, behaviors of the variable defined in the study. Purposive sampling is also explored in the study since it refers to the expert sampling or judgmental. It is a sample of non-probability. The study comprised One Hundred (100) respondents only. Results show that it encourages, open communication and sincerity of teachers for students to be comfortable in sharing their knowledge and opinion inside the classroom in terms of student interest, provides learning reflection for students to gauge quickly in the understanding of the lesson and teaching content in terms of learning reflection, assesses the teaching concept to modify the lesson as needed in terms of direct instruction, provides a better brainstorming approach to learning activities for students to share their insights and ideas about the lesson in terms of learning activities, aligns the learning instruction and standard in the task to the measurable learning target of the subject in terms of student performance. On the other hand, contribution of teacher model theory shows being patient at all levels in the variety of classroom cultural background, intellectual abilities, and learning styles to balance their own expectations and unique abilities for the learners in the area of teacher as talented, shows that teacher improves classroom behavior, student performance, positive attitude, and lead better evaluation in teaching in the area of teacher as enthusiastic, focuses on the transformation and interdisciplinary learning that equips with technological advancement in the increased roles and functions of the learning process in the area of teacher as adaptable, shows that teaching empowers the opinion and ideas that express unique ways in teaching and active learning relevant for student learners in the area of teacher as creative, shows that teacher speaks the truth by avoiding giving false compliments and honestly correcting mistakes done by the students in the area of teacher as honest, shows that it explores student thinking in efficient learning and delivers the information that lasts for the students’ skills and knowledge in the area of teacher as effective, shows that teaches positive skepticism to students and the ability to look for the development and solution to the learning process in the area of teacher as resourceful. Findings show that there is no significant relationship between the teaching and learning intervention in the educational setting implementation and the contribution of the teacher theory model in adapting the teaching and learning intervention in the educational setting among the respondents.